Pendampingan Pemberian Kompres Water Tepid Sponge pada Perawat dengan Kasus DHF di RS Permata Medika Semarang - Wahyuningsih Wahyuningsih; Tri Sakti Widyaningsih; Siti Zubaedah; Nanik Sulistyowati (PPNI UNIMMAN, 2024)
Hyperthermia is a condition of failure to regulate body temperature (thermoregulation) due to the body's inability to release or remove heat or excessive heat production by the body with heat release at a normal rate. Determine nursing problems that arise in patients based on the results of the assessment, determine interventions, carry out implementation according to the plans that have been determined and evaluate the actions / implementations that have been carried out. In accordance with the problems experienced by these partners, efforts have been made, among others, by implementing the implementation of a water tepid sponge in pediatric patients who experience hyperthermia who are treated in the pediatric ward. The specific target of this PKM activity is to teach mothers of child patients who experience hyperthermia, but through education by nurses in the children's ward. water tepid sponge therapy can reduce milk quickly and prevent fever, especially in pediatric patients who experience hyperthermia at Permata Medika Hospital Semarang. Teach the nurse in the pediatric ward how to reduce fever by using a water tepis sponge and the nurse will later educate the parents of child patients with fever. The method used in this PKM activity is to apply the implementation of a water tepid sponge in pediatric patients who experience hyperthermia. Demonstration of water tepid sponge according to SOP. The result of this community service activity is that the level of knowledge of nurses and parents of patients who experience hyperthermia at Permata Medika Hospital in Semarang has increased after being given material on reducing fever management, besides that the patient is able to carry out a simulation on how to reduce fever with a water tepid sponge.